Mesoscale simulations of spherulite growth during isothermal crystallization of polymer melts via an enhanced 3D phase-field model - Li, Weidong (2023)
A finite difference-based 3D phase-field model is developed to investigate the spherulite growth at the mesoscopic scale during the isothermal crystallization of polyamide (PA) 12. The model introduces a phase-field variable to distinguish the crystalline and amorphous phases of polymers. The phase-field evolution equation is coupled with the heat conduction equation that considers the latent heat of crystallization. The evolution equations introduce both the dimensionless diffusivity and latent heat that are dependent on the crystallization temperature. A high-order finite difference-based numerical framework is applied to the phase-field model. Both the qualitative simulation results of the phase-field model such as the crystal morphologies and the quantitative results including the radial crystal growth rate, degree of crystallinity, and lamellar thickness are validated against experiments. The simulation for single-crystal growth shows that a high crystallization temperature results in a large crystal with a slow radial growth rate. The simulation for multi-crystal growth shows that the crystals impinge on each other and finally fill the whole domain during crystallization, which further demonstrates the capability of the model in simulating the spherulite growth during isothermal crystallization of polymer melts.